Application Of Artificial Intelligence In Indonesian Debate Education Game - Hanif Kukuh Raharjo; Andi Nurfita F; Nurya Fahru Rosyidin; Tito Waluyo Purboyo; Ratna Astuti Nugrahaeni (CEPAT Journal of Computer Engineering: Progress, Application and Technology, 2022)
Over time, educational games that exist is increasing. It is very unfortunate that there are some educational games that are too focused on the educational aspect so that they forget their identity as games that aim to relieve fatigue. This research was conducted to avoid this problem. To provide an interesting experience from the game being played, the artificial intelligence system is implemented, the first one is Bezier Curve Algorithm. An algorithm that forms a curve trajectory that will become a cross motion of obstacles. Finite State Machine for the Non-Player Character (NPC) behavior. The last one is Fuzzy Mamdani algorithm, it is an algorithm that will be used in calculating the score in the game. By applying all the algorithm to some aspects of the game, there will be an interesting experience in every game play, because one gameplay will not be similar to the previous one. This game was developed on the Android platform. The test was conducted on 33 high school/vocational high school students with the age range (15-20 years). The results obtained, 97% of respondents agree that the game is interesting for them and 90.9% feel interested in Indonesian debate after playing the game.